A Negative Rational Pigs Game and its Applications to Website Management - Jiang, Dianyu; Shao, Yabin; Zhu, Xiaoyang (Games Review, 2016)
In order to study the balance relation between individual interests and its negative effects, based on a simple rational pigs game to allow robbing food whose negative game system is given by the axiomatic method. The research results are that a system regulation-free will lead to malignant states due to individuals’ immediate interests and that in a system with regulation, a bad equilibrium situation can change into a equilibrium situation with the best public welfare by adjusting some indices. An application to website management shows that the conclusion of this paper conforms to actual situations.